PENGARUH KURS, EKSPOR, DAN IMPOR TERHADAP JUMLAH UANG BEREDAR DI INDONESIA DENGAN INFLASI SEBAGAI VARIABEL MODERATING 2011-2017 - , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 2 No 1 (2018): Bilancia : Jurnal Ilmiah Akuntansi, 2018)
This research aims to determine and analyze the influence of currency on the money supply in Indonesia for the period of 2011-2017, to determine and analyze the influence of export on the money supply in Indonesia for the period of 2011-2017, to determine and analyze the influence of import on the money supply in Indonesia for the period of 2011-2017, to determine and analyze the influence of inflation on the money supply in Indonesia for the period of 2011-2017(moderating variable), to determine and analyze the influence of export and inflation on the money supply in Indonesia for the period of 2011-2017 (moderating variable), and to determine and analyze the influence of import and inflation on the money supply in Indonesia for the period of 2011-2017 (moderating variable). The research results stated that currency influences the money supply in Indonesia for the period of 2011-2017, export and import do not affect the money supply in Indonesia for the period of 2011-2017, currency and inflation not as moderating variable affect the money supply in Indonesia for the period of 2011-2017, export and inflation not as moderating variable affect the money supply in Indonesia for the period of 2011-2017, and import and inflation not as the moderating variable affect the money supply in Indonesia for the period of 2011-2017. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh kurs terhadap jumlah uang beredar Indonesia tahun 2011 -2017, untuk mengetahui dan menganalisis pengaruh ekspor terhadap jumlah uang beredar Indonesia tahun 2011 -2017, untuk mengetahui dan menganalisis pengaruh impor terhadap jumlah uang beredar Indonesia tahun 2011 -2017, untuk mengetahui dan menganalisis pengaruh kurs dengan inflasi terhadap jumlah uang beredar Indonesia tahun 2011 -2017 (variabel moderating), untuk mengetahui dan menganalisis pengaruh ekspor dengan inflasi terhadap jumlah uang beredar Indonesia tahun 2011 -2017 (variabel moderating), dan untuk mengetahui dan menganalisis pengaruh impor dengan inflasi terhadap jumlah uang beredar Indonesia tahun 2011 -2017 (variabel moderating). Hasil penelitian ini menghasilkan penelitian diantaranya adalah kurs berpengaruh terhadap jumlah uang beredar Indonesia tahun 2011 -2017,ekspor dan impor tidak berpengaruh terhadap jumlah uang beredar Indonesia tahun 2011 -2017, kurs dengan inflasi tidak sebagai variabel moderating yang mempengaruhi terhadap jumlah uang beredar Indonesia tahun 2011 -2017,ekspor dengan inflasi tidak sebagai variabel moderating yang mempengaruhi terhadap jumlah uang beredar Indonesia tahun 2011 -2017, danImpor dengan inflasi tidak sebagai variabel moderating yang mempengaruhi terhadap jumlah uang beredar Indonesia tahun 2011 -2017.